ANALYSIS OF LIQUIDITY PROFITABILITY AND DEBT TO EQUITY RATIO ON COMPANY VALUE - Maulana Rizki; Nor Norisanti; Resa Nurmala (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study analyzes the effect of profitability, liquidity, and debt to equity ratio (DER) on firm value in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The main problem identified is the decline in company value in this sector caused by the COVID-19 pandemic and low demand for property. This study aims to determine how much influence the three variables have on firm value. The method used is quantitative with a descriptive-associative approach, using secondary data from the financial statements of companies listed on the IDX and purposive sampling technique to select 9 issuers as samples. Data analysis was carried out through descriptive analysis, correlation test, and multiple regression analysis using SPSS. The results show that profitability has a significant positive effect on firm value, while liquidity has no significant effect. In contrast, DER has a significant negative effect on firm value. High profitability increases investor confidence in the company's prospects, while high DER decreases the value of the company due to increased financial risk. These results imply that companies in the property and real estate sector need to increase profitability and manage capital structure well to increase firm value.